2018
DOI: 10.1177/0162643417746373
|View full text |Cite
|
Sign up to set email alerts
|

Using Multimedia to Teach Self-Regulated Strategy Development to Preservice Teachers

Abstract: The National Commission on Writing called for a reform in writing instruction over a decade ago. However, teacher preparation programs still rarely provide sufficient training in writing instruction for teacher candidates. The purpose of this study was to improve the writing instruction of preservice teachers. Participating preservice teachers ( N = 166) from three universities were randomly assigned to learn essential components of the self-regulated strategy development (SRSD) and the “model it” stage via co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Like prior studies using CAP-TV to help support preservice teachers’ implementation of EBPs (e.g., Alves et al, 2017; Ely et al, 2014; Ely, Pullen, Kennedy, Hirsch, & Williams, 2014; Romig et al, 2017), we also found that the participants who learned about vocabulary practices by viewing CAP-TVs improved implementation of those practices, using them with greater frequency and for longer duration (i.e., for more of their total lesson time). Our study expands on this by demonstrating that receiving performance feedback in addition to CAP-TVs resulted in more improvement in the CAP-TV group’s use of the EBPs than in the comparison groups.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Like prior studies using CAP-TV to help support preservice teachers’ implementation of EBPs (e.g., Alves et al, 2017; Ely et al, 2014; Ely, Pullen, Kennedy, Hirsch, & Williams, 2014; Romig et al, 2017), we also found that the participants who learned about vocabulary practices by viewing CAP-TVs improved implementation of those practices, using them with greater frequency and for longer duration (i.e., for more of their total lesson time). Our study expands on this by demonstrating that receiving performance feedback in addition to CAP-TVs resulted in more improvement in the CAP-TV group’s use of the EBPs than in the comparison groups.…”
Section: Discussionsupporting
confidence: 78%
“…This application is consistent with the existing literature on the use of the CT Scan tool in feedback/coaching settings (Kennedy et al, 2017; Kennedy, Rodgers, Romig, Mathews, & Peeples, 2018; Romig et al, 2017). The CT Scan also stores observation data and visual outputs to allow coaches and teachers to view a teacher’s performance changes over time.…”
Section: Using Performance Feedback To Support a Cognitive Apprenticesupporting
confidence: 88%
See 1 more Smart Citation
“…Content acquisition podcasts (CAPs) have been used with both pre- and in-service teachers with promising results. In a recent randomized control trial, Romig et al (2018) found that pre-service teachers who used CAP-TVs vs lecture or reading demonstrate significant improvements in their writing instruction. Pre-service teachers also report a preference for CAPs, reporting overall satisfaction as well as their usefulness for teaching students with disabilities (Kennedy et al, 2014).…”
Section: Evidence For Coached Componentsmentioning
confidence: 99%
“…Coaches may also decide to use available premade tools, such as resources from the IRIS center (https://iris.peabody.vanderbilt.edu) or Content Acquisition Podcasts for Teachers with Embedded Modeling Videos (CAP-TVs), a series of videos that provide instruction on evidence-based vocabulary instruction (Romig et al, 2018; www.spedintro.com). Another useful resource is the High-Leverage Practice (HLP) website, which contains numerous text-based and video resources (https://highleveragepractices.org/).…”
Section: Technology-based Classroom Observationsmentioning
confidence: 99%